Clinical-epidemiological features of meningococcal infection in children during sporadic morbidity - G. P. Martynova; I. A. Kutishcheva; Ya. A. Bogvilene; N. F. Kuznetsova; A. V. Karasev; E. B. Bojtsova (Журнал инфектологии, 2015)
Purpose: to evaluate epidemiologic situation as to meningococcal infection and reveal clinical-epidemiological features of the disease on the territory of Krasnoyarsk сity and Krasnoyarsk Krai at the present stage. Data and methods: The research gives the analysis of MI morbidity and mortality rates in children of the region according to official information from the Federal Service for Supervision of Consumer Rights Protection and Human Welfare in Krasnoyarsk Krai for the period 2000–2014. The work studies clinical and epidemiological features of the disease in 53 patients with the generalized form of meningococcal infection (GFMI) who were treated in the infectious disease department of the Regional Interdistrict Children’s Clinical Hospital of Krasnoyarsk for the period 2010–2014. Results: The epidemiological situation as to MI in Krasnoyarsk for the period 2000-2013 years is characterized by the signs of interepidemic period with morbidity rises in the winter-spring period. Children from 1 year to 3 years (54,7%) prevail over all MI diseased. The number of children in the first year of life decreased almost two times (from 40% to 20,7%). At the same time the proportion of children older than 4 years increased. The leading serotype among laboratory-confirmed cases of MI in Krasnoyarsk Krai is still the B group meningitis (64,7%). Conclusion: On the territory of Krasnoyarsk Krai the MI morbidity is sporadic. The generalized forms of meningococcal infection are characterized by early overt symptoms which make it possible to set a diagnosis. The clinical picture of the generalized forms of the disease almost did not change significantly.